2018
DOI: 10.3389/fnmol.2018.00191
|View full text |Cite
|
Sign up to set email alerts
|

The New *G29A and G1222A of HCRTR1, 5-HTTLPR of SLC6A4 Polymorphisms and Hypocretin-1, Serotonin Concentrations in Migraine Patients

Abstract: Migraine is one of the most common primary headache disorders that affects 11% of the adult population. The disease is divided into two main clinical subtypes: migraine with aura (MA) and migraine without aura (MO). Both serotonergic and hypocretinergic systems are involved in the migraine pathomechanism. Polymorphisms in the serotonin transporter gene (SLC6A4) and the hypocretin receptor 1 gene (HCRTR1) may be risk factors for migraine development due to their ability to affect serotonin and hypocretin-1 (HCR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 46 publications
0
19
0
Order By: Relevance
“…For comparison group f, ictal vs interictal also refers to the active cluster bout vs remission. In addition to the references from Table 3 with clear blood specimen descriptions (n = 30), 15 references were included 21,26,27,37,39,43,48,125‐132 . Abbreviations: chronic cluster headache (CCH); chronic migraine (CM); control (CTRL); episodic cluster headache (ECH); female/female‐dominated (F/FD); migraine (M); both sexes (M/F); male/male‐dominated (M/MD); migraine with aura (MWA); migraine without aura (MWoA).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…For comparison group f, ictal vs interictal also refers to the active cluster bout vs remission. In addition to the references from Table 3 with clear blood specimen descriptions (n = 30), 15 references were included 21,26,27,37,39,43,48,125‐132 . Abbreviations: chronic cluster headache (CCH); chronic migraine (CM); control (CTRL); episodic cluster headache (ECH); female/female‐dominated (F/FD); migraine (M); both sexes (M/F); male/male‐dominated (M/MD); migraine with aura (MWA); migraine without aura (MWoA).…”
Section: Resultsmentioning
confidence: 99%
“…Findings of abnormalities of the 5‐HT metabolism in migraine patients have varied extensively across studies 17,26,37 . All possible outcomes of 5‐HT were observed in the qualitative synthesis, even for the same stratum within a subgroup.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The result revealed that 5‐HT was significantly increased in VM patients compared to that in control group. Of note, partially different from our result, in a recent study by Kowalska et al, migraine patients were selected according to the ICHD‐3 criteria. MA patients (migraine with aura) and MO patients (migraine without aura) were further divided.…”
Section: Discussionmentioning
confidence: 99%